THE INFLUENCE OF BUREAUCRATIC REFORM, HUMAN RESOURCE STRENGTHENING, AND DIGITALIZATION ON EXCELLENT CIVIL SERVANTS THROUGH EMPLOYEE MOTIVATION AS A MEDIATING VARIABLE - Prayogo, Sulung Anom; Hendayana, Yayan; Hidayat, Wastam Wahyu; Renwarin, Joseph M J; Eprianto, Idel (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the influence of bureaucratic and governance reforms, human resource (HR) strengthening, and digitization and information technology on the realization of a superior Civil Service (ASN), with employee motivation as a mediating variable. Method: The study was conducted within the Directorate General of Budget (DJA) of the Ministry of Finance, using a quantitative approach with the Structural Equation Modeling based on Partial Least Squares (SEM-PLS) method. Data was collected through a questionnaire administered to 344 DJA employees. Results: The results of the hypothesis testing indicate that bureaucratic reform and governance (β = 0.178; t = 2.326), HR strengthening (β = 0.394; t = 4.704), and digitalization (β = 0.164; t = 1.948) have a significant positive effect on employee motivation. Employee motivation also significantly influences high-quality civil service human resources (β = 0.372; t = 7.278). Additionally, employee motivation significantly mediates the relationship between the three independent variables and high-quality civil service human resources, although the indirect effect of digitalization is relatively smaller (β = 0.061; t = 1.870). Novelty: These findings confirm that the success of bureaucratic transformation is not only determined by technical policies but also by psychological aspects such as work motivation. This study contributes to the development of public sector human resource management policies based on strengthening employees' intrinsic and extrinsic motivation.